Evaluation of flatulence of Uterus (Nafkhat-ol-rahem) as One of the Causes of Infertility in Women from the Viewpoint of Ali ibn Abbas Ahvazi and Modern Medicine - Golfakhabadi, Fereshteh; Zaheri Abdevand, Zeinab; Tansaz, Mojgan (Journal of Contemporary Medical Sciences, 2020)
Objective: Today Infertility and its complications is one of the largest problems because it would impose economic burden and psychological pressure on the people. One of the infertility reasons in most Iranian Traditional medicine (ITM) manuscripts is focused on Nafkhat-ol-rahem. Methods: In this study, the Ibn Abbas theories in kamel al- Sina'ah about Nafkhat-ol-rahem, causes, reasons and treatment were investigated. To achieve recent studies, searches were performed in the databases with the keywords including vaginal flatus, vaginal flatulence and pelvic floor weakness. Results: This disease is caused by bad cold temper, hit and obstruction of cervix, etc. Traditional medicine considered the bloating of uterus (Nafkhat-ol-rahem) the cause of some miscarriages and infertility, because dense gas that accumulated in the uterus, preventing implantation and establishment of the embryo. In ITM, treatment involves the use of warm and mohallel riyah (gas dissolvent) herbal medicines in the form of oral, poultice (topical ointment), Forzajeh and Homol (vaginal suppository). Conclusion: Nafkhat-ol-Rahem is a highly prevalent disease in women, but because of the shame, the patient does not speak with her doctor. Bloating of uterus and vaginal flatulence seen in the pelvic floor muscle relaxation, which can be harmless or associated with major complications such as rectovaginal fistula and infection of the uterus.